(3dhGeY GdCSQGQ TQM eWGdY GdCSQGQs - (3GdQGRj, GdbWH GdJMJGfj, eMeO Hf eMeO, (B766 (3g`s ((3ChjS Hf COjHs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg ajGV PhGQa GdYhGQa hHYO aEf GdYdhe Ydi JTYH afhfgG hJcKQ TLhfgG hCQaY GdeWGdH hYde GdefWb ef HjfgG hGNJQJ cJGH GdeWGdY efgG deG QCjJ GdCUMGH jgJehf HOQSg hjSCdhffj Cf CTQMg aCNPJ aj TQM dg hSejJgG dhGeY GdCSQGQ aj TQM eWGdY GdCfhGQs
(3BNQgG (B:s
(3Ke YQV dg GdZdW aj GdacQ agh LOjQ HCf jgLQ GdMceI dG jchf eSJYO dOQc MbGFb GdCTjGA hcd ejSQ deG Ndb dgs
(3aj Ghdg fbhd hagQSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 38s
(3eYLe GdeDdajf (B3 / 642s
(3cTa GdXfhf (B2 / 1716s
(3TPQGJ GdPgH (B6 / 207s
Keywords: (3GdadSaI hGdefWbs